Расчет контактных давлений в механических системах с помощью программы Comsol Multiphysics - Байда, Е.И. (Електротехніка і електромеханіка, 2013)
У статі розглянута методика розрахунку контактного тиску в осях механічних систем за допомогою пакета програм Comsol Multiphysics. In the article, a calculation technique for contact pressure in the
axes of mechanical systems based on Comsol Multiphysics
package is considered.